Longitudinal development of pain sensitivity in adolescent non-suicidal self-injury - Koenig, Julian; Gaber, Lena; Parzer, Peter; Resch, Franz; Kaess, Michael (Journal of psychiatric research, 2017)
Nonsuicidal self-injury (NSSI) is associated with reduced pain sensitivity (PS). Existing theories posit that altered PS is a risk factor for NSSI. Cross-sectional data suggest that PS normalizes in those terminating self-injury. However, previously no study addressed the longitudinal course of PS in patients engaging in NSSI. We addressed changes in PS and clinical symptomatology in adolescents with NSSI (n = 18) and matched controls (n = 19) over one year. Despite significant clinical improvements, PS did not change in the NSSI group but decreased in controls. Greater NSSI reduction was associated with increased pain tolerance. Findings are discussed in the light of current theories on PS in NSSI.